Bibliometric Analysis of Educational Research in 2017 to 2021 using VOSviewer: Google Scholar indexed Research - Husaeni, Dwi Fitria Al; Nandiyanto, Asep Bayu Dani; Maryanti, Rina (Indonesian Journal of Teaching in Science, 2023)
Education is the study of a group of people's knowledge, abilities, and habits, which is passed down from generation to generation through teaching, training, or research. The goal of this study is to combine mapping analysis with VOSviewer software to undertake a bibliometric analysis of research in the field of education. To acquire research data, the reference manager application is employed. The information gathered is based on search results for the term "education." From the search results, we found 993 articles that were published between 2017 and 2021. According to the findings, the number of studies in 2017 was 232, grew to 263 in 2018, and then continued to fall from 2019 to 2021. In 2021, there will be 39 education-related research publications published in Google Scholar indexed journals. The fundamental reason is that the Covid-19 pandemic has had a significant impact on educational research, as practically everything is focused on Covid-19. The value of bibliometric analysis in providing analytical data about what happens is demonstrated in this work. This study is meant to assist and serve as a resource for researchers in researching and identifying research themes.